Enhance: a Service Learning model for sustainability - Sabina Falconi (Firenze University Press, 2023)
The article reports the experience of the modeling of Service Learning proposed by the European project Enhance (A220-HED-57E82F65), based on two competence frameworks, the Green Comp (Bianchi, Pisiotis, & Cabrera Giraldez, 2022) and Career Management Skills (ELPGN, 2015). The use of these frameworks allows design for learning outcomes, evaluation of student experience and attribution of micro-credentials. The ultimate goal of the project concerns the promotion of a model that integrates the emergence of a mind set for individual sustainability with a system approach that favors the integration of the University with the territory to promote practices functional to the green transition.   Enhance: un modello di Service Learning per la sostenibilità. L'articolo riporta l'esperienza della modellizzazione del Service Learning proposta dal progetto europeo Enhance (A220-HED-57E82F65), basato su due framework di competenze, il Green Comp (Bianchi, Pisiotis, & Cabrera Giraldez, 2022) e le Career Management Skills (ELPGN, 2015). L'uso di questi framework permette una progettazione per learning outcomes, la valutazione dell'esperienza degli studenti e l'attribuzione di microcredenziali. Il fine ultimo del progetto riguarda la promozione di un modello che integra l'emergere di un mindset per la sostenibilità individuale con un approccio di sistema che favorisce l'integrazione dell'Università con il territorio per promuovere pratiche funzionali alla transizione verde.